2015
DOI: 10.5194/acp-15-4215-2015
|View full text |Cite
|
Sign up to set email alerts
|

The decrease in mid-stratospheric tropical ozone since 1991

Abstract: Abstract. While global stratospheric O 3 has begun to recover, there are localized regions where O 3 has decreased since 1991. Specifically, we use measurements from the Halogen Occultation Experiment (HALOE) for the period 1991-2005 and the NASA Aura Microwave Limb Sounder (MLS) for the period 2004-2013 to demonstrate a significant decrease in O 3 near ∼ 10 hPa in the tropics. O 3 in this region is very sensitive to variations in NO y , and the observed decrease can be understood as a spatially localized, yet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 32 publications
(36 reference statements)
3
40
0
Order By: Relevance
“…8 certainly does emphasize is that the anomalies over Lauder at 10 hPa during the period 2004-2014 are not, predominantly, driven by a decadal-scale global trend. Nedoluha et al (2015) showed that O 3 variations at the equator are very strongly positively correlated to variations in N 2 O. This relationship could best be understood as resulting from dynamical variations.…”
Section: Unusually High Mid-stratospheric O 3 From August 2009 Througmentioning
confidence: 99%
See 4 more Smart Citations
“…8 certainly does emphasize is that the anomalies over Lauder at 10 hPa during the period 2004-2014 are not, predominantly, driven by a decadal-scale global trend. Nedoluha et al (2015) showed that O 3 variations at the equator are very strongly positively correlated to variations in N 2 O. This relationship could best be understood as resulting from dynamical variations.…”
Section: Unusually High Mid-stratospheric O 3 From August 2009 Througmentioning
confidence: 99%
“…This relationship could best be understood as resulting from dynamical variations. Using a 2-D chemical transport model, Nedoluha et al (2015) showed that slower ascent resulted in more N 2 O being photodissociated and oxidized to produce NO x (while reducing N 2 O), and the increased NO x destroyed more ozone, resulting in a positive correlation between O 3 and N 2 O. Such a relationship has been previously deduced from changes in HALOE measurements of NO 2 at ∼ 10 hPa from 1993 to 1997, where the change in NO 2 was shown to be consistent with a decrease in upward transport (Nedoluha et al, 1998).…”
Section: Unusually High Mid-stratospheric O 3 From August 2009 Througmentioning
confidence: 99%
See 3 more Smart Citations